Anti-corruption Bodies in Algeria their Role in Protecting Public Money - لحرش أيوب التومي (Milev Journal of Research and Studies, 2020)
Through this study, we aim to shed light on anti-corruption bodies in Algeria their role in protecting public money, by knowing the competencies legally conferred on these mechanisms and powers that the legislator has granted to the national authority for the prevention and combating of corruption alike, with the aim of knowing how effective these are mechanisms in protecting public funds and achieving the deterrence and anti-corruption function in Algeria, and thus to what extent have the bodies charged with combating corruption contributed to protecting public money in Algerian legislation? To find out, we follow the analytical method to enrich the topic